Can Dual-Class Shares Thrive in Indonesia’s Capital Market? A Legal Comparison with Asia’s Financial Powerhouses - Pati, Umi Khaerah; Pratama, Anugrah Muhtarom (Pandecta Research Law Journal, 2024)
The introduction of dual-class shares (DCS) in Indonesia, particularly for technology startups, aims to foster innovation and enhance market competitiveness by allowing firms to retain control while accessing capital. This study investigates the implementation of multiple voting shares (MVS) within the DCS framework as outlined in POJK Number 22/POJK.04/2021, analyzing its effectiveness in Indonesia compared to other Asian financial hubs like Hong Kong and China, and offering a comparative legal analysis with the United States and Singapore. The findings reveal that despite the potential of DCS, Indonesia’s capital market faces challenges, including the reluctance of companies to adopt this structure due to stringent requirements such as market capitalization and audited revenue, which often impede startups from going public. In contrast, countries like the United States and Singapore have adopted a more flexible approach, omitting such requirements, making the DCS model more attractive. The research underscores the urgency for Indonesia to reconsider its regulatory approach to technology startups and capital market access. The novelty of this study lies in its comparative analysis across diverse jurisdictions, identifying legal and regulatory barriers to the successful adoption of DCS in Indonesia. This study contributes to the discourse by proposing a hybrid regulatory approach, suggesting that market capitalization and audited revenue should only be considered when sustainability points cannot be quantified, as practiced in the United States and Singapore. Such a shift could help Indonesia foster a more dynamic and inclusive capital market, encouraging the growth of technology startups while maintaining investor protection and market stability.